Drug design. - Ariens, E. J. (Everhardus Jacobus) (Medicinal chemistry (Academic Press), 1972)
Drug Design, Volume III covers the mode of action of biologically active compounds. The book discusses microbial transformations that have been used in the preparation of drugs or closely related substances; the use of linear free energy parameters and other experimental constants in structure-activity studies; and the mode of action of anticoagulants structurally and functionally related to vitamin K. The text also describes the design of beta-blocking drugs, biologically active acridines, local anesthetics, and insect chemosterilants. The molecular approach for designing inhibitors to enzym.